Influenza virus infection among pediatric patients reporting diarrhea and influenza-like illness - Dilantika, Charisma; Sedyaningsih, Endang R; Kasper, Matthew R; Agtini, Magdarina; Listiyaningsih, Erlin; Uyeki, Timothy M; Burgess, Timothy H; Blair, Patrick J; Putnam, Shannon D (BMC infectious diseases, 2010)
Background Influenza is a major cause of morbidity and hospitalization among children. While less often reported in adults, gastrointestinal symptoms have been associated with influenza in children, including abdominal pain, nausea, vomiting, and diarrhea. Methods From September 2005 and April 2008, pediatric patients in Indonesia presenting with concurrent diarrhea and influenza-like illness were enrolled in a study to determine the frequency of influenza virus infection in young patients presenting with symptoms less commonly associated with an upper respiratory tract infection (URTI). Stool specimens and upper respiratory swabs were assayed for the presence of influenza virus. Results Seasonal influenza A or influenza B viral RNA was detected in 85 (11.6%) upper respiratory specimens and 21 (2.9%) of stool specimens. Viable influenza B virus was isolated from the stool specimen of one case. During the time of this study, human infections with highly pathogenic avian influenza A (H5N1) virus were common in the survey area. However, among 733 enrolled subjects, none had evidence of H5N1 virus infection. Conclusions The detection of influenza viral RNA and viable influenza virus from stool suggests that influenza virus may be localized in the gastrointestinal tract of children, may be associated with pediatric diarrhea and may serve as a potential mode of transmission during seasonal and epidemic influenza outbreaks.